Direct Molecular Diagnosis of CYP21A2 Point Mutations in Macedonian and Serbian Patients with 21-Hydroxylase Deficiency - Anastasovska Violeta; Milenković Tatjana; Kocova Mirjana (Society of Medical Biochemists of Serbia, 2015)
Steroid 21-hydroxylase deficiency is present in 90-95% of all cases with congenital adrenal hyperplasia (CAH), an autosomal recessive disorder. It can present as the severe classical salt wasting (SW) or simple virilising (SV) form, or the milder, nonclassical form. Nine pseudogene-derived point mutations account for about 80% of all defects in the CYP21A2 gene coding the 21-hydroxylase enzyme.